Impact of Financial and Non-Financial Rewards on Employee Motivation of Nepalese Insurance Companies - Shrestha, Abhishek; Wagle, Bibek; Lama, Dipak (Nepalese Journal of Economics, 2024)
This study examines the impact of financial and non-financial rewards on employee motivation in Nepalese insurance companies. Employee motivation is the dependent variable. The independent variables are recognition, flexible working hour, salary, bonus and job security. The primary source of data is used to assess the opinions of the respondents regarding financial and non-financial rewards and level of motivation in Nepalese insurance companies. The study is based on primary data which were collected from 120 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The regression models are estimated to test the significance and importance of financial and non-financial rewards on employee motivation in Nepalese insurance companies. The result shows that recognition has a positive impact on employee motivation. It indicates that higher the recognition, higher would be the employee motivation. Similarly, there is a positive impact of flexible working hour on employee motivation. It indicates that better flexibility in working hours leads to increase in employee motivation. The result also shows that salary has a positive impact on employee motivation. It indicates that better the salary, higher would be the employee motivation. Likewise, bonus has a positive impact on employee motivation. It indicates that increase in bonus leads to increase in employee motivation. In addition, job security has a positive impact on employee motivation. It indicates that higher the job security, higher would be the employee motivation in Nepalese insurance companies.